Religious motivation and personality of Indian Canossian Sisters in three stages of formation - Mathew, Maggie (M. Elengkal), FDCC. (Animo Repository, 1993)
This study investigated the level of religious motivation and personality profile of the Canossian Sisters in India classified into three stages of formation, the novitiate, the juniorate and the on going formation. The descriptive correlational research design was utilized. Data were collected by the use of two questionnaires, the Religious Motivation Questionnaire (Menguito, 1990) and Gordon Personal Profile.The following hypotheses were presented:1) There is a significant difference in the levels of religious motivation among the novices, juniors, and seniors.2) There is a significant difference among the three groups in their personality profile.3) There is a significant relationship between religious motivation and personality of the Canossian Sisters. The sample selected for this study were 30 novices, 27 juniors and 34 seniors from the province of Mary Immaculate, South India, between the age limit of 19 to 61. One Way ANOVA was used to compare the religious motivation and personality of the three groups. Pearson's Product Movement Correlation was done to establish the relationship between religious motivation and personality. A significant relationship was observed between religious motivation and personality (F = .241, P .05) across the three groups. Significant differences were found between the groups in some of the factors of personality. There was the significant difference between the novices and seniors in Ascendancy (P 0.01). Again, significant difference was indicated between the novices and seniors and juniors and seniors in responsibility (P 0.01). There was also a significant difference between the novices and seniors in sociability (P 0.01) and between juniors and seniors (P .05).Based on the findings, it can be stated that there is a tendency to improve in responsibility as the Canossian Sisters go through the different stages of formation while there is a significant decline in positive personality traits like Ascendancy and Sociability as the novices, move on to the juniorate and finally live their on going formation.